Social Commerce Purchase Intention Factors in Developing Countries : A systematic literature review - Adi Suryaputra Paramita (Journal of Applied Engineering and Technological Science (JAETS), 2023)
Over the last decade, research on social commerce has grown exponentially, reflecting the widespread adoption of social commerce strategies and practices. Social commerce encompasses a broad range of distinct concepts. Recent reviews of the literature detail the numerous factors of social commerce adoption. This paper has an objective to investigate the important factor of social commerce adoption in developing countries. 149 articles from high quality repository collected to be review, in this study the systematic literature review conducted through Kitchenham methodology which consist of developing research question, determining the sources as well as research string, categorizing inclusion and exclusion criteria, choosing the primary studies, extracting the data then synthesizing the data. After careful quality assessment process, 49 articles selected to process in depth review. The result of this study found that there ae several important factors and lead by trust factor for social commerce adoption in developing countries.